Cell localization of the anti-inflammatory protein annexin 1 during experimental inflammatory response. - Oliani, S. M. [UNESP]; Perretti, M. [UNESP] (My University, 2001)
The localization of the glucocorticoid-inducible protein annexin 1 (ANX-1) in leukocytes during the process of experimental inflammation has been studied using immunocytochemistry. ANX- 1 immunoreactivity was detected in extravasated neutrophils and eosinophils as well as in resident tissue mast cells. Following injection of carrageenin, the mesenteric tissue was highly inflamed with large presence of leukocytes (predominantly neutrophils with a small percentage of eosinophils) adherent to post-capillary venules and extravasated in the perivascular tissue. ANX-1 immunoreactivity was detected in the cytosol of neutrophils and eosinophils mainly associated with granules and/or vesicles. A good degree of localization in the endosomes was observed in the neutrophils. In both cell types, some ANX-1 immunoreactivity in the nucleus and in the plasma membrane was also detected. Resident mast cells were also activated. Mast cells were positive for ANX-1, without apparent changes in protein content in relation to their activation status. Degranulated mast cells still presented ANX-1 associated with the granule matrix. In conclusion, this study demonstrated the presence of ANX-1 in leukocytes that play a central role in the host inflammatory response. These are the extravasating polymorphonuclear cells, or the resident mast cells. These data provide morphological support to the notion that endogenous and exogenous ANX-1 are able to modulate the reactivity of these cell types, and more generally, of the experimental inflammatory reaction.